The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12872-015-0121-2
|View full text |Cite
|
Sign up to set email alerts
|

TSC-22 up-regulates collagen 3a1 gene expression in the rat heart

Abstract: BackgroundThe transforming growth factor (TGF)-β is one of the key mediators in cardiac remodelling occurring after myocardial infarction (MI) and in hypertensive heart disease. The TGF-β-stimulated clone 22 (TSC-22) is a leucine zipper protein expressed in many tissues and possessing various transcription-modulating activities. However, its function in the heart remains unknown.MethodsThe aim of the present study was to characterize cardiac TSC-22 expression in vivo in cardiac remodelling and in myocytes in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Qun Chen et al reported that NEAT1 bind to EZH2 to suppress the Wnt signaling pathway and thereby regulated Glioblastoma progression[ 49 ]. Considering that our in vitro cellular model of cardiac fibrosis was stimulated using TGF-β1, and Smad7 is a very classical key antagonist of the reported TGF-β1/Smad2/3 signaling pathway [ 50 , 51 ], which is normally considered to inhibit Smad2, Smad3, and Smad4 [ 52 ], thereby suppressing the progression of many fibrotic diseases, has also been reported to be inhibited by binding to EZH2 [ 53 ]. Therefore, we chose Smad7 as a downstream molecule for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Qun Chen et al reported that NEAT1 bind to EZH2 to suppress the Wnt signaling pathway and thereby regulated Glioblastoma progression[ 49 ]. Considering that our in vitro cellular model of cardiac fibrosis was stimulated using TGF-β1, and Smad7 is a very classical key antagonist of the reported TGF-β1/Smad2/3 signaling pathway [ 50 , 51 ], which is normally considered to inhibit Smad2, Smad3, and Smad4 [ 52 ], thereby suppressing the progression of many fibrotic diseases, has also been reported to be inhibited by binding to EZH2 [ 53 ]. Therefore, we chose Smad7 as a downstream molecule for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming Growth Factor Beta-1-Induced Transcript 4 Protein (Tsc22; upregulated in MCT RV: protein = 3.82-fold, transcript = 2.1-fold) Tsc22 regulates alpha smooth muscle actin, PAI-1, fibronectin and collagen I, contributing to myocardial fibrosis ( Yan et al, 2011 ). Tsc22 is also upregulated in the left ventricle of spontaneously hypertensive rats (SHR), in experimental myocardial infarction models and in models of LVH caused by chronic pressure overload driven by either arginine vasopressin or angiotensin II ( Kelloniemi et al, 2015 ). While adenoviral overexpression of TCS22 failed to significantly regulate many heart failure-relevant transcripts (including brain natriuretic peptide, Anp, Il6 and Col1a), it did elicit a robust increase in Col3a1 in the LV.…”
Section: Discussionmentioning
confidence: 99%